Electronic load as part of the test complex of the power processing unit of electric and plasma propulsion; IOP Conference Series: Materials Science and Engineering; Vol. 177 : Mechanical Engineering, Automation and Control Systems (MEACS 2016) - Chubov S. V. (Information technologies in Mechanical Engineering, 2017)
Title screen